Workshop report (Journal of Face Aesthetics, 2024)
The workshop provided an in‑depth introduction to the principles of traditional Chinese medicine, focusing on the fundamentals of acupuncture and acupressure. Participants gained valuable insights into the pathways of various meridians located on the head and neck, equipping them with essential knowledge to better understand energy flow within the body.
Keywords: workshops; report; Chinese medicine